Two new species of the genus Khorata (Araneae: Pholcidae) from China - Wei, Xiao; Xu, Xiang (Zootaxa, 2014)
Two new species of Khorata are described from China: K. ningyuan sp. nov. and K. sancai sp. nov. Both species were collected in caves.